Epidemiology and outcomes from out-of-hospital cardiac arrests in England. (January 2017) - Hawkes, Claire; Booth, Scott; Ji, Chen; Brace-McDonnell, Samantha J.; Whittington, Andrew; Mapstone, James; Cooke, Matthew W.; Deakin, Charles D.; Gale, Chris P.; Fothergill, Rachael; Nolan, Jerry P.; Rees, Nigel; et al.
Abstract: Introduction: This study reports the epidemiology and outcomes from out-of-hospital cardiac arrest (OHCA) in England during 2014. Methods: Prospective observational study from the national OHCA registry. The incidence, demographic and outcomes of patients who were treated for an OHCA between 1st January 2014 and 31st December 2014 in 10 English ambulance service (EMS) regions, serving a population of almost 54 million, are reported in accordance with Utstein recommendations. Results: 28, 729 OHCA cases of EMS treated cardiac arrests were reported (53 per 100, 000 of resident population). The mean age was 68.6 (SD = 19.6) years and 41.3% were female. Most (83%) occurred in a place of residence, 52.7% were witnessed by either the EMS or a bystander. In non-EMS witnessed cases, 55.2% received bystander CPR whilst public access defibrillation was used rarely (2.3%). Cardiac aetiology was the leading cause of cardiac arrest (60.9%). The initial rhythm was asystole in 42.4% of all cases and was shockable (VF or pVT) in 20.6%. Return of spontaneous circulation at hospital transfer was evident in 25.8% (n = 6302) and survival to hospital discharge was 7.9%. Conclusion: Cardiac arrest is an important cause of death in England. With less than one in ten patients surviving, there is scope to improve outcomes. Survival rates were highest amongst those who received bystander CPR and public access defibrillation.